Performance of VLCC Ship with Podded Propulsion System and Rudder - Koto, Jaswar; Amin, Amirul (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Podded propulsion system becomes common installed in ships due to high maneuvering. The purpose of this paper is to discuss performance of both VLCC ships with podded propulsion and rudder. As initial offset data, published ship (SR221A) was used for generating hull form of a podded propulsion ship using Maxsurf software by maintaining the principal dimension: length, breadth, and draft. In order to suit installation of podded house, the stern part was modified. The hydrostatic data of both ships with podded propulsion and rudder are transferred to Ship Resistance and Propulsion Simulation software to determine the running speed by given same power. It was found that running speed produced by a ship using pod propulsion system lower than the speed produced by a ship using rudder.